Genetics, linguistics, and prehistory : thinking big and thinking straight - Sims-Williams, Patrick
Many claims have been made linking ancient languages with genetically identified prehistoric and modern populations. There is much new 'evidence' and intense debate on the validity and appropriateness of such interdisciplinary work. Here Patrick Sims-Williams provides a timely comment on linguistics and the quest for ancient populations.